Peningkatan Keterampilan SDM Wirausaha Baru Dalam Menggali Potensi Lokal Desa Kragan dan Peningkatan Literasi Penggunaan Digital Marketing Bagi Masyarakat Desa Kragan [Enhancing the Skills of New Entrepreneurial Human Resources in Exploring Local Potential of Kragan Village and Increasing Literacy in the Use of Digital Marketing for the Community of Kragan Village] - Riyanto, Mohammad Aqil; Adinugroho, Mukhtar; Fatimah, Nuzulul; Putra, Riyan Sisiawan; Irhamni, Firly (UKInstitute, 2025)
Abstract. Kragan Village, located in Gedangan District, Sidoarjo Regency, is an area with significant local potential, but still faces several challenges in entrepreneurship development, particularly in the use of digital technology. Low levels of digital literacy and managerial skills are major barriers for aspiring entrepreneurs in effectively managing and marketing their products. Therefore, this community service program aims to strengthen the capacity of entrepreneurs through training in business skills and digital marketing. The methods used include planning, training implementation, ongoing mentoring, and participatory evaluation. The results of this program indicate that the village community is beginning to recognize the strategic benefits of digital marketing and is able to apply it in managing their businesses. This program has successfully increased technology awareness, expanded market access, and supported the sustainable strengthening of the village economy. This activity also aligns with the institution's research roadmap and the scientific direction of the Management study program and is expected to serve as an example of community empowerment that focuses on local potential and digital technology. Abstrak. Desa Kragan Gedangan yang terletak di Kecamatan Gedangan, Kabupaten Sidoarjo adalah daerah dengan potensi lokal yang besar, namun masih menghadapi beberapa tantangan dalam aspek pengembangan kewirausahaan, terutama dalam hal penggunaan teknologi digital. Rendahnya tingkat pemahaman digital dan keterampilan manajerial menjadi penghalang utama bagi para wirausaha pemula untuk mengelola dan memasarkan produk mereka dengan baik. Oleh sebab itu, kegiatan pengabdian masyarakat ini bertujuan untuk memperkuat kapasitas para wirausaha melalui pelatihan dalam bidang keterampilan bisnis dan pemasaran digital. Metode yang digunakan mencakup langkah-langkah perencanaan, pelaksanaan pelatihan, pendampingan secara berkelanjutan, dan evaluasi partisipatif. Hasil dari kegiatan ini menunjukkan bahwa masyarakat desa mulai menyadari keuntungan strategis dari pemasaran digital, serta dapat menerapkannya dalam pengelolaan usaha mereka. Program ini telah berhasil meningkatkan kesadaran terhadap teknologi, memperluas akses pasar, dan mendukung penguatan ekonomi desa secara berkelanjutan. Kegiatan ini juga sejalan dengan peta jalan penelitian lembaga dan arah keilmuan program studi Manajemen, serta diharapkan dapat menjadi contoh pemberdayaan masyarakat yang berfokus pada potensi lokal serta teknologi digital.